Influence of aspect in soil and vegetation water dynamics in dry Mediterranean conditions: functional adjustment of evergreen and semi-deciduous growth forms - Gabarrón-Galeote, Miguel Angel; Ruiz-Sinoga, José Damián; Quesada, Miguel a (Ecohydrology, 2012)
This study was undertaken in a watershed at a dry Spanish Mediterranean location. The effects of the north-facing and southfacing aspects on atmospheric parameters, soil water contents (SWCs) and plant water balances were assessed during 18 months including two dry seasons and one wet season. The species studied were the evergreen sclerophyll Quercus suber and the semideciduous shrubs Cistus albidus, Cistus monspeliensis and Lavandula stoechas. Atmospheric parameters were similar in both exposures, but water content of the 30-cm uppermost soil layers was higher under canopy in the south-facing slope during the wet season. Water balances of both slopes were different, and this was related to the lower shrub abundance and the vegetation patchiness observed in the south-facing slope. Autumn plant recovery was faster in the north-facing hillslope and occurred ﬁrst in shrubs. During the whole study, Quercus suber displayed a hydrostable strategy maintaining an optimum water balance in both hillslopes. This was not the case of shrubs that avoided drought using a phenological adjustment and were more affected by aspect. Differences between tree and shrub water economies relied mainly on their respective root systems. The faster recovery of shrubs after the ﬁrst autumn rainfalls allows them to avoid competition with other functional groups for water and nutrients during some days. Leaf-drying curves distinguished the functional behaviour of the tree and the shrubs because stomatal closure occurred at higher relative water content in the former. The coexistence of both functional strategies ensures an efﬁcient use of water and nutritional resources
Keywords: accepted 18 february 2012; aspect; cistus; lavandula; Mediterranean; plant water balance; Quercus; received 23 may 2011; revised 12 december 2011; Soil moisture

Pathways for resilience in Mediterranean cork oak land use systems - Acácio, Vanda; Holmgren, Milena (Annals of Forest Science, 2012)
& Context Loss of woodlands and degradation of vegetation and soil have been described for all Mediterranean-type ecosystems worldwide. In the Western Iberian Peninsula, overexploitation of evergreen cork oak land use systems has led to soil erosion, failures in oak recruitment, and loss of forests. Degraded and dry sites are quickly colonised by pioneer heathland rockrose (Cistus spp.) shrubs forming highly persistent patches. & Aims Although traditionally shrublands have been considered as a transient successional state, we present evidence that they can represent persistent alternative states to former cork oak forests. & Review trends and conclusions We first describe how Mediterranean vegetation evolved in the Iberian Peninsula and the role of fire and long-term human management as main disturbances. We then discuss alternative pathways through state-and-transition models indicating the ecological and land use variables that halt cork oak regeneration and recruitment and drive vegetation transitions towards persistent shrublands. Unless concerted management actions and restoration programmes are undertaken, the cork oak land use systems will not be sustainable.
Keywords: alternative stable state; cistus; mediterranean-type ecosystem; Quercus suber; resilience; Restoration

Vegetation and soil seed bank relationships across microhabitats in an abandoned Quercus suber parkland under simulated fire - Torres, Ivan; Urbieta, Itziar R; Moreno, Jose M (Ecoscience, 2012)
Mediterranean agro-forestry systems are undergoing rapid change due to abandonment. This turns formerly cultivated or grazed oak-tree parklands (i.e., savanna-type formations called “dehesas”) into flammable formations of scattered trees within a matrix of shrubs with open spaces. Wildfires can now occur, threatening the persistence of these formations. Fire-prone shrublands commonly regenerate after fire from seeds stored in the soil. Understanding the relationships between standing vegetation and the soil seed bank across microhabitats can help predict the response of the system in case of fire. Here we investigated these relationships in an abandoned Quercus suber (cork oak) dehesa in central Spain. Vegetation and soil were sampled and assigned to different microhabitats: under the trees (TRC), in dense shrub cover (DSC), and in low shrub cover (LSC). A heat shock was applied to half of each sample to simulate fire; the other half served as control. Both sets of samples were then germinated in a greenhouse. Almost 90% of the species were herbs, while the rest were woody shrubs. The number of species recorded in TRC and DSC was lower than in LSC, in which species richness, particularly herbs, was maximal. Heating increased the total number of species that germinated, but mean species richness per sample was not altered. Heating markedly increased the number of germinations in all microhabitats, particularly those of woody species. Furthermore, the germination of shrubby species increased in the 3 microhabitats, notably in TRC. While the standing plant community was well differentiated among microhabitats, this was not the case for the soil seed bank, which was homogeneous across microhabitats, with or without heating. We conclude that the high density of shrubby seeds found in TRC or in the other microhabitats presents substantial threats to the persistence of Q. suber parklands in case of fire.
Keywords: cistus; Cork oak; Dehesa; Encroachment; Erica; Mediterranean shrublands

Relationship between net photosynthesis and leaf respiration in Mediterranean evergreen species - Gratani, L; Varone, L; Catoni, R (Photosynthetica, 2008)
The relationship between net photosynthetic (PN) and leaf respiration (R) rates of Quercus ilex, Phillyrea latifolia, Myrtus communis, Arbutus unedo, and Cistus incanus was monitored in the period February 2006 to February 2007. The species investigated had low R and PN during winter, increasing from March to May, when mean air temperature reached 19.2 °C. During the favourable period, C. incanus and A. unedo had a higher mean PN (16.4±2.4 µmol m −2 s −1 ) than P. latifolia, Q. ilex, and M. communis (10.0±1.3 µmol m −2 s −1 ). The highest R (1.89±0.30 µmol m −2 s −1 , mean of the species), associated to a significant PN decrease (62 % of the maximum, mean value of the species), was measured in July (mean R/PN ratio 0.447±0.091). Q10, indicating the respiration sensitivity to short-term temperature increase, was in the range 1.49 to 2.21. Global change might modify R/PN determining differences in dry matter accumulation among the species, and Q. ilex and P. latifolia might be the most favoured species by their ability to maintain sufficiently higher PN and lower R during stress periods.
Keywords: arbutus; cistus; Myrtus; Phillyrea; Q10; Quercus; seasonal course; temperature.

Adaptive photosynthetic strategies of the Mediterranean maquis species according to their origin - Gratani, L; Varone, L (Photosynthetica, 2004)
In consideration of their origin the adaptive strategies of the evergreen species of the Mediterranean maquis were analysed. Rosmarinus officinalis L., Erica arborea L., and Erica multiflora L. had the lowest net photosynthetic rate (PN) in the favourable period [7.8±0.6 µmol(CO2) m -2 s -1 , mean value], the highest PN decrease (on an average 86 % of the maximum) but the highest recovery capacity (>70 % of the maximum) at the first rainfall in September. Cistus incanus L. and Arbutus unedo L. had the highest PN during the favourable period [15.5±5.2 µmol(CO2) m -2 s -1 , mean value], 79 % decrease during drought, and a lower recovery capacity (on an average 54 %). Quercus ilex L., Phillyrea latifolia L., and Pistacia lentiscus L. had an intermediate PN in the favourable period [9.2±1.3 µmol(CO2) m -2 s -1 , mean value], a lower reduction during drought (on an average 63 %), and a range from 62 % (Q. ilex and P. latifolia) to 39 % (P. lentiscus) of recovery capacity. The Mediterranean species had higher decrease in PN and stomatal conductance during drought and a higher recovery capacity than the pre-Mediterranean species. Among the pre-Mediterranean species, P. latifolia had the best adaptation to long drought periods also by its higher leaf mass per area (LMA) which lowered leaf temperature thus decreasing transpiration rate during drought. Moreover, its leaf longevity determined a more stable leaf biomass during the year. Among the Mediteranean species, R. officinalis was the best adapted species to short drought periods by its ability to rapidly recover. Nevertheless, R. officinalis had the lowest tolerance to high temperatures by its PN dropping below half its maximum value when leaf temperature was over 33.6 °C. R. officinalis may be used as a bioindicator species of global change.
Keywords: arbutus; cistus; drought period; Erica; Phillyrea; Pistacia; Quercus; recovery capacity; Rosmarinus; Stomatal conductance